(untitled) (Nepalese Journal of Management Research, 2022)
This Research was done to analyse the buying behaviour of frozon foods in Chitwan district. The data was obtained from the questionnaire and analysed with the help of different tabular presentations along with their graphs. The three hundred respondents of different age group was selected to find the relevant data. The researcher found that majority of consumer of Frozen foods is male and for occupations are concern, businesspersons have greater number in comparison with other occupation. Majority of consumer drinking Frozen foods in Chitwan district is of the age group of 20-50 years.